Wpływ Długości Rozciąganych Osiowo Prętów Stalowych na ich Wytrzymałość - Jastrzębski, P. (Engineering Transactions, 1961)
The scale effect found its theoretical explanation first in the works of W. WEIBULL, [4], [51] and then in those of J. FRENKIEL and T. KONTOROVA, [1]. These publications concern, however brittle materials (including the phenomenon of brittle rupture of metals) for which the scale effect is of greatest importance. The main object of the present paper is to determine experimentally the functional relation between the length L and the strength R or the yield point Q of steel bars subject to axial tension. The author proposes, on the basis of the laboratory tests carried out by himself, the use of the Eqs, (2.2). and (2.3) represented graphically (as an example) by Figs. 2-4. The numerical values of the parameters, for some steel types, are contained in Table 6. A method is proposed for generalizing the test results (concerning test pieces of some ½/ m) to practically important cases of bars of greater length (of some tens of meters). The long bar is treated as a chain (Fig. 11) of which the links are the test pieces. A metallographic analysis confirms the statement that the principal cause of the scale effect is the non-homogeneity of materials. In conclusion, 2 method for reducing the admissible stress is given, depending on the length of the bar.